As metáforas de semelhança na construção de referentes discursivos: qual a orientação argumentativa? - Menezes, Léia Cruz de (2011)
In the 80's, Lakoff and Johnson's work presented a new vision of the metaphor's nature to the world. Metaphor is now understood as a figure of thought. As part of our conceptual system, the study of metaphorical expressions allows us to depict the emotional and affective aspects in the constitution of the discursive referents, thus enabling us to a better understanding of the values underlying the representations of social “objects” in a given socio-historical moment. Based on this premise, we analyze the constitution and argumentative orientation of resemblance metaphor expressions used by Ricardo Noblat's blog readers along the discussion of Isabella Nardoni's police case.